KONSENTRASI LOGAM BERAT (CD DAN PB) PADA SEDIMEN PERMUKAAN PERAIRAN TELUK BAYUR PROVINSI SUMATERA BARAT INDONESIA - Nanci Aulia Safitri; Rifardi Rifardi; Rasoel Hamidy (Program Pascasarjana Universitas Riau, 2009)
The purpose of this study is to clarify the ecosystem quality of Bayur Bay based on heavymetalic elements (Cd and Pb) behaviour in surface sediment. Sediment samples were collectedusing grab sampler from 4 stasions in Bayur Bay , West Sumatera Province, Indonesia in Marchto April 2009. Surface sediment samples were used for the mechanical analysis by the settling-tube method, and mean size diameter was calculated based on the proportion of grain-sizedistribution. Concentration of Cd and of Pb in the samples were determined using AutomicAbsorption Spectrofotimetry (ASS). One Way Analysis Variance (ANOVA) was carried to clarifythe relation between the concentration of Cd, Pb and mean size diameter of sediment. Generaltrend of Cd and Pb distribution strongly indicate that the ecosystem quality of Bayur Bay is insame level for all stations as shown by result of one way anova (Tcalculate < Ttabel). The studyarea is under influence of human activities supplied Cd and Pb to the surface sediment. Resultsof linier regression analysis show negative correlation between Cd concentration and mean sizediameter (Y = -0.031x + 1.262). Contrastingly, correlation between Pb concentration and meansize diameter shows positive value (Y = 0,098x - 0,10). Cd and Pb concentrations in surfacesediment of Bayur Bay are lower than the ERL (Effect Range Low: Cd = 1,2 ppm; Pb = 46,7ppm) and ERM (Effect Range Median: Cd = 9,6 ppm; Pb = 218 ppm) indicating the Bayur Bayecosystem is not yet polluted by the concentrations.